Territorios, margen y los mapas de la fragmentación. La creación de sujetos de desarrollo y sujetos de marginalidad. (2017)
The article aims to problematize the conditions of subjects who are subjected to socioeconomic contexts through the development / progress dichotomy. For this, in the first place, it was conceptualized on the different theoretical positions on the territory from its physical, social and anthropological conceptions. Secondly, the theory of progress and growth developed by the development model has been problematized, which has reconfigured the notion of “subjects of rights” to emerge from themselves “subjects of development”. Finally, there are scenarios of vulnerability and marginality, which give rise to marginal subjects, product of the limits and fragments of the territories and the margins that dehumanize them.